121 Rate of Perioperative Neurological Complications After Surgery for Cervical Spinal Cord Stimulation. (1st August 2016) - Kai-Hong Chan, Andrew; Winkler, Ethan A.; Jacques, Line
Abstract: INTRODUCTION: Cervical spinal cord stimulation (cSCS) is used to treat pain of the cervical region and upper extremities. Case reports and small series have shown a relatively low risk of complication after cSCS, with only 2 reported cases of perioperative spinal cord injury in the literature. Catastrophic cSCS-associated spinal cord injury remains a concern as a result of underreporting. To aid in preoperative counseling, it is necessary to establish a minimum rate of spinal cord injury and surgical complication following cSCS. METHODS: The National Inpatient Sample (NIS) is a stratified sample of 20% of all patient discharges from nonfederal hospitals in the United States. We identified discharges with a primary procedure code for spinal cord stimulation ( International Classification of Diseases, Ninth Revision 03.93) associated with a primary diagnosis of cervical pathology from 2002 to 2011. We analyzed short-term safety outcomes including the presence of spinal cord injury and neurological, medical, and general perioperative complications and compared outcomes using univariate analysis. RESULTS: Between 2002 and 2011, there were 2053 discharges for cSCS. The spinal cord injury rate was 0.5%. The rate of any neurological, medical, and any general perioperative complication was 1.1%, 1.4%, and 11.7%, respectively. There were no deaths. CONCLUSION: In the largest series of cSCS, the risk of spinal cord injury was higher than previously reported (0.5%). Nonetheless, this procedure remains relatively safe, and physicians may utilize these data to support the safety of cSCS in an appropriately selected patient population. This may become a key treatment option in an increasingly opioid-dependent, aging population.